Visualizing the Data City Social Media as a Source of Knowledge for Urban Planning and Management - Ciuccarelli, Paolo; Lupi, Giorgia; Simeone, Luca.; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2014)
This book investigates novel methods and technologies for the collection, analysis, and representation of real-time user-generated data at the urban scale in order to explore potential scenarios for more participatory design, planning, and management processes. For this purpose, the authors present a set of experiments conducted in collaboration with urban stakeholders at various levels (including citizens, city administrators, urban planners, local industries, and NGOs) in Milan and New York in 2012. It is examined whether geo-tagged and user-generated content can be of value in the creation of meaningful, real-time indicators of urban quality, as it is perceived and communicated by the citizens. The meanings that people attach to places are also explored to discover what such an urban semantic layer looks like and how it unfolds over time. As a conclusion, recommendations are proposed for the exploitation of user-generated content in order to answer hitherto unsolved urban questions. Readers will find in this book a fascinating exploration of techniques for mining the social web that can be applied to procure user-generated content as a means of investigating urban dynamics.
Introduction -- We Live in Informational Landscapes -- Depicting the Data City -- Methodological Framework -- Working in the Field -- Reflections on Potentialities and Shortcomings of Geo-Located Social Media Analysis -- List of Case Studies Used for Building the Matrix -- Excerpts from Conversations with Accurat, Lust and Mobivery.
Keywords: Computer science; Data mining; Regional planning; Urban planning; Graphic design; Computer Science; Data Mining and Knowledge Discovery; Landscape/Regional and Urban Planning; Graphic Design; Electronic books